Analysis of Russian pharmaceutical specialists labor market for 2019–2022 - D. V. Kurkin; Yu. S. Knyazeva; O. V. Ivanova; Yu. A. Kolosov; Yu. V. Gorbunova; D. A. Bakulin; I. S. Krysanov; D. L. Klabukova; M. A. Javakhyan; V. I. Zvereva; N. A. Lycheva; V. N. Shoich; et al. (Фармация и фармакология (Пятигорск))
The higher education system is becoming more and more competitive every year. It faces ambitious tasks of training highly qualified personnel and ensuring technological sovereignty. A labor market analysis is an integral component of the early career guidance work with students and their navigation in the profession, which is especially important at the beginning of their employment.The aim of the work was to conduct a comparative analysis of supply and demand indicators in the labor market of pharmaceutical specialists in nine Russian regions in 2019–2022.Materials and methods. The research methodology included the collection, quantitative and qualitative analyses of the data on the SuperJob.ru website. The posted offers (vacancies) and CVs were analyzed on the portal SuperJob.ru (a large online service of CVs and vacancies from direct employers, agencies, employment centers) for 2019–2022 in nine regions and federal districts of Russia: Moscow and the Moscow region, St. Petersburg and the Leningrad region, the Central Federal District (without the Moscow region), the Northwestern Federal District (without the Leningrad Region), the Volga Federal District, the Urals Federal District, the Siberian Federal District, the Far Eastern Federal District, the Southern and North Caucasus Federal Districts.Results. The analysis of the number of posted vacancies and CVs in the recruitment agency database for 2019–2022 shows a stable shortage of pharmacy professionals with both secondary (vacancies / CVs – 42112 / 41037) and higher professional education (vacancies / CVs – 36432 / 25149). The pointed out specialists are among the most required ones by employers, and pharmacy is one of the most popular areas for candidates. Cities with a high level of economy and population experience a greater deficit in specialists with pharmaceutical education. Salary levels of specialists with higher or secondary education are almost comparable on average from 50 to 75 thousand rubles, but employers generally prefer to hire specialists with higher education.Conclusion. On average in the regions, the demand for specialists with higher education is lower than the demand for specialists with secondary education and the salary expectations of pharmacists coincide with the employers’ offers, while the salary expectations of specialists with higher education are higher in the market. Specialists with secondary education are much more numerous, as they are trained by a much larger number of educational institutions. For pharmacy technicians, a pharmacy is often the only place of work in their specialty, while for pharmacists it is usually a starting point.